Job stress and its determinants among academic staff in a Malaysian public university - Muhamad Zaki, Nor Amalina (2016)
Background: Job stress occurs when there is a conflict between the workplace or workload and an individual’s ability to cope with the situation. There are plenty of studies on job stress among academic staff were conducted, but most of the time, the higher education been neglected and ignored from the study. Academic staff of higher education were believed to be stress free, but recently, researchers found that there is increase of job stress level among academic staff of higher education. Objective: The objective of this study is to determine job stress and its determinants among academic staff in Universiti Putra Malaysia, Serdang. Methodology: This is a cross-sectional study and it was conducted in Universiti Putra Malaysia, Serdang. Systematic sampling method was used to select the subjects. A total of 421 permanent local lecturers participated in this study. Ethical approval was obtained from Ethics Committee for Research involving Human Subjects of Universiti Putra Malaysia (JKEUPM), and written consent was obtained from all participants. Selected lecturers were given NIOSH Generic Job Stress Questionnaire and The Workplace Stress Questionnaire; and were given 1 to 2 weeks to complete and return the questionnaire. Result: The study shows that 6.2% of the respondents had severe job-related stress and most of them (54.6%) reported moderate job-stress. There were 59.4% of the respondents who reported with job stress were female while 40.6% of the respondents who reported with job stress were male. Most (60.5%) of the respondents who reported with job stress were between 26 to 40 years old (60.5%). About 85.2% of the respondents who reported with job stress were married and 85.2% of them also reported to have children to be take care of. Most of the respondents with job stress (49.2%) reported to have to work between 45 to 60 hours per week. When tested singly, gender, hours of work, workload and responsibility at workplace, and social support from supervisor were significantly related with job stress where p<0.05. The Binary logistic regression showed that hours of work AOR (45 to 60 hours per week =2.339; >60 hours per week = 1.174), 95% CI lower (45 to 60 hours per week = 1.287; >60 hours per week = 0.680), 95% CI upper (45 to 60 hours per week =4.253; >60 hours per week = 2.029), workload at workplace and responsibility at workplace (AOR = 1.190, 95% CI lower = 1.098, 95% CI upper = 1.291) are significantly related to job stress. Conclusion and recommendation: Hours of work, workload and responsibility at workplace are the determinants of job stress among academic staff in Universiti Putra Malaysia, Serdang. University management should plan stress prevention program for lecturers. Further studies investigate further on these determinants. A cohort study recommended for a more conclusive result.